Signal Transducer and Activator of Transcription 3 - a promising target in colitis-associated cancer - Pandurangan, Ashok Kumar; Mohd Esa, Norhaizan (Asian Pacific Education Press Ltd., 2014)
Colorectal cancer (CRC) is the third most common malignancy and fourth most common cause of cancer mortality worldwide. Untreated chronic inflammation in the intestine ranks among the top three high-risk conditions for colitis-associated colorectal cancer (CAC). Signal Transducer and Activator of Transcription 3(STAT3) protein is a member of the STAT family of transcription factors often deregulated in CRC. In this review, we try to emphasize the critical role of STAT3 in CAC as well as the crosstalk of STAT3 with inflammatory cytokines, nuclear factor (NF)-κB, PI3K/Akt, Mammalian Target of Rapamycin (mTOR), Notch, Wnt/β-catenin and microRNA (MiR) pathways. STAT3 is considered as a primary drug target to treat CAC in humans and rodents. Also we updated the findings for inhibitors of STAT3 with regard to effeects on tumorigenesis. This review will hopefully provide insights on the use of STAT3 as a therapeutic target in CAC.